The Existence of Railway Transportation in the Cirebon Region, 1900–1942 - Ninda Lutfianti; Ponco Setiyonugroho; Yusuf Budi Prasetya Santoso (Historia, 2026)
The need for transportation in the Cirebon region in the early twentieth century was primarily driven by the limited means of transporting plantation products, particularly sugarcane, to the port as the center of export distribution. At that time, the dominant mode of transport was the railway. Interestingly, since the 1900s Cirebon had two types of rail services, namely conventional trains and trams. Their existence not only accelerated the mobilization of plantation products but also reduced transportation costs, which had previously relied on traditional overland means. The role of the railway was highly significant for the sugar industry, as Cirebon was one of the key regions in the sugarcane plantation network in Java. However, the use of railways was not limited to sugar entrepreneurs. Over time, the railway network also served the mobility needs of the general population, both in terms of passenger transport and the shipment of other trade commodities. This study employs the historical method, which includes the stages of heuristics, source criticism, interpretation, and historiography. This approach allows for a systematic examination of archival records, company reports, and colonial documents related to the dynamics of transportation in Cirebon. The findings reveal that the railway system in Cirebon was not only a vital infrastructure supporting the colonial plantation economy but also transformed into a public facility that accelerated urbanization, expanded local trade networks, and enhanced socio-economic mobility. Therefore, the railway in Cirebon played a dual role: as a key driver of the colonial plantation-based economy and as an instrument of transportation modernization that connected Cirebon with other regions in Java.